SOCIO-ECONOMIC SUSTAINABILITY ASSESSMENT OF MULTI-STOREY HOUSING: A SKYVILLE @ DAWSON SINGAPORE CASE STUDY - Tanuwidjaja, Gunawan; Bastian, Ermyra Putri; Tedja, Jason Maynard; Prasetyo, Ivan Reagan; Adiasih, Priskila (Border: Jurnal Arsitektur, 2024)
Social and economic sustainability significantly affect the well-being of residents in high-rise vertical housing. Previous research has identified various complaints about poor relationships between residents, lack of interaction, and feelings of confinement. On the other hand, COVID-19 has limited interactions among residents in densely populated housing due to the high transmission rates of the disease. This study aims to conduct a content analysis of data on Skyville @ Dawson apartments from reliable sources, covering the period from 2009 to 2024. The research is conducted with the content analysis method, focusing on economic, social, and environmental aspects of Sustainable Architectural Design. From secondary and online data, it was found that WOHA designed Skyville @ Dawson to accommodate the behavioral needs of Singaporean society with several horizontal gardens on various floors, potentially securing interaction against COVID-19 through good building management. Therefore, this high-rise housing is an excellent example of the socio-economic development of upper-floor housing.